2020
DOI: 10.1098/rspa.2020.0077
|View full text |Cite
|
Sign up to set email alerts
|

Placing limits on long-term variations in quiet-Sun irradiance and their contribution to total solar irradiance and solar radiative forcing of climate

Abstract: Recent reconstructions of total solar irradiance (TSI) postulate that quiet-Sun variations could give significant changes to the solar power input to Earth's climate (radiative climate forcings of 0.7–1.1 W m −2 over 1700–2019) arising from changes in quiet-Sun magnetic fields that have not, as yet, been observed. Reconstructions without such changes yield solar forcings that are smaller by a factor of more than 10. We study the quiet-Sun TSI si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 63 publications
(167 reference statements)
3
22
0
Order By: Relevance
“…The cap on the rise in TSI since the Maunder minimum derived here, 2.0 ± 0.7 W m −2 , encloses all the current estimates (Coddington et al, 2016; Dasi‐Espuig et al, 2016; Egorova et al, 2018; Judge et al, 2012; Lockwood & Ball, 2020; Schrijver et al, 2011; Shapiro et al, 2011; Steinhilber et al, 2009; Tapping et al, 2007; Wu et al, 2018) except the range of 3 to 6.3 W m −2 indicated by Shapiro et al (2011), the reassessment of their model by Judge et al (2012), and CHRONOS (Egorova et al, 2018) (Figure 1b). We consider the upper limit established here to be more reliable than the existing estimates.…”
Section: Comparison To Other Estimates Of the Change In Tsi Since Thesupporting
confidence: 86%
See 3 more Smart Citations
“…The cap on the rise in TSI since the Maunder minimum derived here, 2.0 ± 0.7 W m −2 , encloses all the current estimates (Coddington et al, 2016; Dasi‐Espuig et al, 2016; Egorova et al, 2018; Judge et al, 2012; Lockwood & Ball, 2020; Schrijver et al, 2011; Shapiro et al, 2011; Steinhilber et al, 2009; Tapping et al, 2007; Wu et al, 2018) except the range of 3 to 6.3 W m −2 indicated by Shapiro et al (2011), the reassessment of their model by Judge et al (2012), and CHRONOS (Egorova et al, 2018) (Figure 1b). We consider the upper limit established here to be more reliable than the existing estimates.…”
Section: Comparison To Other Estimates Of the Change In Tsi Since Thesupporting
confidence: 86%
“…The other model‐based estimates (Coddington et al, 2016; Dasi‐Espuig et al, 2016; Steinhilber et al, 2009; Tapping et al, 2007; Wu et al, 2018) are markedly weaker and relatively consistent with one another, indicating a rise of between 0.3 and 0.9 W m −2 (Figure 1b). In another recent study, Lockwood and Ball (2020) concluded, from an analysis of the measurements and models of TSI over the past two solar cycles, that it cannot be excluded from the uncertainty in this data that TSI might have been 0.4 W m −2 lower to 0.75 W m −2 higher during the Maunder minimum. Furthermore, there is a claim that the last cycle minimum in 2008 might be representative of the Maunder minimum (Schrijver et al, 2011).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Results from the various SI models show considerable disagreement in the long-term evolution of TSI with estimated changes since the Maunder minimum ranging from 0.7 Wm À2 to 6 Wm À2 (Wang et al, 2005;Krivova et al, 2007Krivova et al, , 2010Tapping et al, 2007;Steinhilber et al, 2009;Shapiro et al, 2011;Vieira et al, 2011;Judge et al, 2012Judge et al, , 2020Egorova et al, 2018;Wu et al, 2018;Lockwood & Ball, 2020). The various SI models also estimate different SSI variations on timescales longer than a few solar rotations (see Ermolli et al, 2013, for a review of this topic).…”
Section: Introductionmentioning
confidence: 99%